Предмет: Алгебра,
автор: ИраДа
x-y=2
{
2x-3y=-1
Ответы
Автор ответа:
0
из первого уравнения х = у + 2. Подставив это выражение во второе уравнение, получаем
2 * (у + 2) - 3 * у = 4 - у = -1.
Тогда у = 5, а х = 5 + 2 = 7
Автор ответа:
0
x-y=2 |*-2
2x-3y=-1
-2x+2y=-4
2x-3y=-1
-------------
-y=-5
y=5
x-5=2
x=7
Похожие вопросы
Предмет: Математика,
автор: khvanvlada2000
Предмет: Алгебра,
автор: baklavariat6152521
Предмет: География,
автор: maks1k75a
Предмет: Математика,
автор: Бестолач
Предмет: Математика,
автор: 25052000